Analysis of Injuries and Risk Factors in Taekwondo during the 2014 Italian University Championship - Fortina, Mattia; Mangano, Simone; Carta, Serafino; Carulli, Christian (Joints, 2017)
Purpose This study aims to analyze the risk factors and type of injuries occurring in Taekwondo athletes participating in a national competition.Methods Out of the 127 competitors, 18 athletes got injured during a Taekwondo championship who were analyzed for the following parameters: modality of training; age, weight; belt color; and the type of injury.Results Around 89% of the injuries were due to bruising and were found mainly on the lower limbs (61%) during the elimination rounds and during the first match of the day. The higher probability of injury was in the second round (56%), and during the first match of the day (72%). Nearly all the athletes were able to complete the game in which they were injured (83%). Comparing the average age of the athletes suffering an injury (23.6 ± 2.06 years) with their average years of training (8.4 ± 7.05 years) it can be noted that these athletes began this discipline rather late. The more is the training age and the weekly hours of training, the more are the numbers of matches completed, even as injured. Beginners with a low-level belt suffered more injuries than the experienced subjects did.Conclusion The following risk factors for injury were found: starting to practice in late age, weekly training sessions with a few number of hours, male sex, low-level belt, elimination rounds, the first match of the day, and second round.Level of Evidence Level III, observational analytic study without a control group.
Keywords: athletic injuries; injury rate; prevention; risk factors; martial arts; Taekwondo